The Trilogy of Linguistic Communication of the Qur’an Surah Al-Kâfirûn - Hasanuddin Chaer; Abdul Rasyad; Ahmad Sirulhaq; Djamil Abdurachman Malik (OKARA: Jurnal Bahasa dan Sastra, 2022)
In Indonesia, the word "al-kâfir" which comes from the Arabic word "al-kâfir" (الكافر) as in the Qur'an surah al-Kâfirûn is often used to offend non-Muslim groups. This study aims to reveal the essence of the meaning of linguistic features in the form of the main word "al-kâfir" and sentence in the first verse of surah al-Kâfirûn, which is still ambiguous, as the word "kâfir" is often only interpreted to non-Muslim people. This study used Jakobson's "interlingual" linguistic translation theory with the "mutual translatability" analysis method. These methods reveal aspects of the equivalent of words and sentences from the source language of the Qur'an to the target language (Indonesian). This study found that the word al-kafir in the first verse of al-Kâfirûn does not only mean to people who are not Muslim but contains meaning to all individuals who are blind to the truth of the Qur'an. Allah taught the linguistics of the Qur'an through Muhammad to all individuals. Thus Allah teaches the meaning of effective and persuasive communication through the trilogy of linguistic communication of surah al-Kâfirûn. As an implication, this finding is expected to reduce the gap in understanding the word "al-Kâfirûn," which sometimes triggers social conflict.